From resistance and control to normative orders: The Wire's Cedric Daniels as an ethical bureaucrat. (March 2022) - Dallyn, Sam; Marinetto, Mike
While the categories of control and resistance have provided important frames of reference to understand workplace relations, we argue that they offer a limited analytical range when investigating conduct in public institutions where work still has sizeable elements of discretion – despite the increasing demands of performance measurement that have been a central component of new public management. Here, we investigate the HBO series, The Wire, and situate it as a piece of social science fiction. By affording more attention to the different 'codes' of policework depicted on the show we develop a more pluralistic understanding of workplace conduct. In tracing out different normative orders that characterize these codes, we consider The Wire 's Cedric Daniels' distinctive positioning in relation to performance measurement and the predominant normative order of 'the numbers game' and argue that he consistently displays the code of an ethical bureaucrat.